Հայ ժողովրդական երգիծական մանրապատում-զվարճախոսությունների թումանյանական գրառումները եւ դրանց տարբերակային դրսեւորումները - Արմեն Շ. Սարգսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Мало кому известно, что первые напечатанные работы известного армянского писателя Ованеса Туманяна были на юмористические темы о лорийских армянах. Фактически дебют писателя осуществляется в области фольклора. Туманяновские записи армянских народных юмористических миниатюр и прибауток ясно показывают, что Ов. Туманян был прямым носителем устной традиции и словестного фольклора своего народа. It is hardly known that the first printed works of the prominent Armenian writer Hovhannes Tumanyan were in humoristic topics towards Lori Armenians. In fact the debut of the writer was realized in the sphere of folcloristic. The Armenian popular jokes recorded by Hovhannes Tumanyan show clearly that Tumanyan had perfectly known the oral tradition and the folklore of his people.
Keywords: Literature; Folklore; Ethnography